White space, black hood : opportunity hoarding and segregation in the age of inequality - Cashin, Sheryll (Beacon Press, 2021)
"A meditation on how America protects and overinvests in "white space" and disinvests, surveils, and stereotypes in "the Hood;" Cashin calls for abolition of these anti-Black processes and bold new investment to repair poor Black neighborhoods and our broken race relations"--